A post-accession crisis? Political developments and public sector modernization in Hungary - György Jenei (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2009)
The paper examines the relationship between the political system and the public administration modernization in the Hungarian transition. Its intention is to point out that there are various shortcuts and bottlenecks of the Hungarian modernization and the cumulative impacts of these deficiencies have caused characteristic difference of the Hungarian modernization trajectory from the typical Western trajectories.
Keywords: H11; H83; 330; Hungarian incomplete modernization trajectory; phases of modernization and their international contexts; politization; Neo-patrimonialism versus Neo-weberian synthesis; EU-Erweiterung; Politische Reform; Verwaltungsreform; Autoritäres System; Ungarn